2023
DOI: 10.1200/jco.22.00264
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Uncertainties of Circulating Tumor DNA in Human Papillomavirus–Related Oropharyngeal Squamous Cell Carcinoma in the Absence of National Comprehensive Cancer Network Guidelines

Abstract: Author affiliations and support information (if applicable) appear at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The multitude of assays, ranging from institutional assays to proprietary commercial assays, vary in substrate used for analysis (ie, saliva, plasma/blood, urine) and molecular detection technique used (ie, quantitative PCR, droplet digital PCR, next generation sequencing). 18,19 Combining these different meth- ods, a recent systematic review and meta-analysis found that in 10 studies, including 457 patients, ctDNA-based assays had a pooled sensitivity of 65% and a specificity of 99% in detecting disease. 20 While the specificity is quite good across assays, the sensitivity is more highly variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multitude of assays, ranging from institutional assays to proprietary commercial assays, vary in substrate used for analysis (ie, saliva, plasma/blood, urine) and molecular detection technique used (ie, quantitative PCR, droplet digital PCR, next generation sequencing). 18,19 Combining these different meth- ods, a recent systematic review and meta-analysis found that in 10 studies, including 457 patients, ctDNA-based assays had a pooled sensitivity of 65% and a specificity of 99% in detecting disease. 20 While the specificity is quite good across assays, the sensitivity is more highly variable.…”
Section: Discussionmentioning
confidence: 99%
“…This unique tumor biology coupled with advances in molecular diagnostic techniques has led to the development of multiple assays to detect HPV ctDNA. The multitude of assays, ranging from institutional assays to proprietary commercial assays, vary in substrate used for analysis (ie, saliva, plasma/blood, urine) and molecular detection technique used (ie, quantitative PCR, droplet digital PCR, next generation sequencing) . Combining these different methods, a recent systematic review and meta-analysis found that in 10 studies, including 457 patients, ctDNA-based assays had a pooled sensitivity of 65% and a specificity of 99% in detecting disease .…”
Section: Discussionmentioning
confidence: 99%
“…Second, cost-effectiveness and insurance reimbursement for routine clinical use without Food and Drug Administration authorization remain unresolved 31 . Finally, it remains unclear how best to incorporate plasma ctDNA into routine surveillance paradigms for HPV + OPSCC established by the National Comprehensive Cancer Network 32 . These areas require clarification before the widespread implementation of ctDNA as a biomarker in clinical practice.…”
Section: Current State Of Liquid Biopsies In Hpv+ Opsccmentioning
confidence: 99%
“…31 Finally, it remains unclear how best to incorporate plasma ctDNA into routine surveillance paradigms for HPV + OPSCC established by the National Comprehensive Cancer Network. 32 These areas require clarification before the widespread implementation of ctDNA as a biomarker in clinical practice.…”
Section: Current State Of Liquid Biopsies In Hpv + Opsccmentioning
confidence: 99%
“…To the Editor Ferrandino et al report clinical performance of plasma tumor tissue–modified viral (TTMV)-human papillomavirus (HPV) DNA in diagnosis and surveillance of HPV-associated oropharyngeal squamous cell carcinoma (OPSCC). The findings highlight the promise of liquid biopsies for improving patient care and the uncertainties around how to integrate these assays with imaging, clinical examinations, and conventional biopsy . The variable time points for plasma TTMV-HPV DNA monitoring limited estimates of lead time detection, suggesting an opportunity for further standardizing timing of liquid biopsy testing protocols.…”
mentioning
confidence: 99%